IMPACT OF EXCLUSIVE BREASTFEEDING EDUCATION ON MATERNAL STRESS REFERRED TO SELECTED HOSPITALS AFFILIATED TO UNIVERSITIES OF MEDICAL SCIENCES IN TEHRAN DURING 2009-2010: Pharmaceutical Sciences-Nursing - KERAMI, AZAM; HAZHIR HEIDARI-BEIGVAND, DR.; MOMENI, HAMID; SALEHI , ASHRAF; PUDINEH SABOUR, FATEMEH; MIRMORADZEHI SIBI, MOZHDEH; ROOHI KARIMI, TACHARA; MIRSHEKARI , MARZIEH; MIRSHEKARI, LEILA (International Journal of Life Science and Pharma Research, 2017)
Breastfeeding saves the lives of more than one and half million infants per year and strengthens the motherchild emotional relationship plays a significant role in their psychosocial development characteristics. This research aims at determining the impact of exclusive breastfeeding education on maternal stress. In this descriptive-comparative clinical trial study, the researcher randomly selected three hospitals from hospitals affiliated to universities of medical sciences with premature infant intensive care unit, and attended in research space in three months. He took samples from eligible mothers and collected data through responding to questionnaire. 100 nulliparous mothers were entered into study and randomly put into two groups of case (n=50) and control (50) groups; and the intervention group was put under the face-to-face education after delivery during a 45-minute session and finally the educational booklets were given to them. Control group did not receive any training program by researcher; and the questionnaires were responded again by samples in both groups a month later. The questionnaire consisted of three parts. The first part was about personal characteristics, and the second one was about perceived stress. Content validity was utilized to determine the validity of first questionnaire. The perceived stress questionnaire contained the standardized tests with approved validity by numerous researchers and psychologists. T Test-Retest was used to determine validity. Data analysis was done by descriptive and inferential statistical software, t-test, Paired ttest, and Chi-square test. According to results of test, there is a significant difference between maternal stress in case group before and after education. Education has a significant effect on mothers’ perceived stress in case group after education (t= 2.20 and p<0.05). Education of exclusive breastfeeding for premature infants reduces the maternal stress and it can be concluded that mothers with premature infants need special breastfeeding education.